Pengaruh Penerapan Isak 35 Terhadap Kualitas Laporan Keuangan Organisasi Sektor Publik - Diaz Rizka Canda Anggraini; Priono Priono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research was conducted to examine the effect of the Application of ISAK 35 on the Quality of Reports of Public Sector Financial Organizations at Educational Foundations in Wringinanom District. This study used quantitative methods with data collection instruments in the form of questionnaires. The population of this study is the management of the Education Foundation in Wringinanom District. Sampling with the criteria of respondents is the chairman of the foundation, deputy chairman of the foundation, secretary of the foundation, and foundations with funds obtained as many as 52 respondents from 13 foundations. Data analysis used in the study included: descriptive analysis, classic assumption test, multiple linear regression analysis, and hypothesis testing using SPSS 27. The results showed that the implementation of ISAK 35 had a significant effect on report quality. Keywords: Application of ISAK 35, Quality of Financial Reports. Public Sector Organization, Educational Foundation.